Exploring Challenges of Peer Feedback in an EFL Micro Teaching Class - Cendani, Imanuela Artika Sekar Ayu; Purnamaningwulan, Rina Astuti (Universitas Lancang Kuning, 2023)
For English as a Foreign Language learners, peer feedback is a useful tool that fosters autonomous learning. Allowing students to give and receive feedback from their peers during Micro Teaching sessions offers an alternative in addition to the input from teachers. It also helps in developing students’ evaluating skill which is a prerequisite of being future teachers. However, if students are still facing difficulties in giving and receiving feedback, the quality of the peer feedback activity cannot be guaranteed. The objective of this study was to investigate the challenges and their underlying factors associated with peer feedback which revealed potential for improvements in the quality of the feedback and the students’ evaluating skills. Data collection was conducted using a case study approach and involved the use of a questionnaire and interviews. A total of eighteen participants partook in the study, with six of them also engaging in interviews. Hesitation in giving comments, changes in power relations, lack of time, and quality differences of the feedback were shown to be the four main challenges in peer feedback. Three primary aspects, which are lack of confidence, ambiguous feedback, and differences in proficiency levels, had an impact on these difficulties. The study's findings indicate that peer feedback should take place within a supportive environment, highlighting the importance of academics providing clear instructions to enhance the effectiveness of the peer feedback process.